Assessment of Frequency and Composition of Renal Stones in a Reference Laboratory of Pakistan - Bibi, Afshan; Aamir, Muhammad; Riaz, Maria; Haroon, Zujaja Hina; Kirmani, Sobia Irum; Javaid, Haroon (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine frequency and chemical composition of renal stones in Northern Pakistan using FTIR Spectroscopy.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jan 2017 to Jul 2020.Methodology: One thousand and twenty-nine stones were analysed in 3 years at AFIP of patients aged from 1 to 98 years. They were analysed by Automatic FT-IR type IRAffinity-1. The results were verified by manual analysis of spectrograms and then confirmed by standard peaks feed on NICODOM LIBRARY.Results: Calcium oxalate stones were the most frequent (1065,80.1%), followed by uric acid stones (179,13.5%), mixed stones (44,3.3%), calcium appetite (31,2.3%), struvite (6,0.5%), hydroxy appetite (1,0.1%) and cysteine stones (3,0.2%). Male predominance was noted in patients with renal stones (1057,79.5%). The majority of the patients were from the age group 21 –40 years (47.5%)Conclusion: Calcium oxalate stones are most commonly followed by uric acid stones in patients of northern Pakistan. The frequency of renal stones is high in male patients.